Finite-time consensus problem of multi-agent systems with disturbance. Issue 12 (August 2016) - Sun, Fenglan; Zhu, Wei; Li, Yongfu; Liu, Feng
Abstract: Finite-time consensus for continuous-time multi-agent systems with disturbance is studied in this paper. By employing the Hölder continuous Lyapunov function, algebraic graph theory and control theory, some sufficient conditions for the finite-time consensus are presented. An example and simulation results are given to illustrate the effectiveness of the presented method and the correctness of the obtained theoretical results.